Pengaruh Kepemilikan Institusional, Ukuran dan Umur Perusahaan Terhadap Praktik Perataan Laba (Studi Kasus Pada Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Christina Burhan, Melissa; Malau, Harman (Akuntansi: Jurnal Akuntansi Integratif, 2021)
Abstract The study aims to examine the effect partially and simultaneously between Institutional Ownership, Firm Size, Age, on Income Smoothing. The research was conducted use quantitative methods. The population in this study is 20 of state-owned companies listed on the IDX during period 2017 to 2019 (3 years). In order to obtain 60 as research sample. The data collected were analyzed and processed with the formula in Microsoft Excel and then using software SPSS 22. The data analysis technique is descriptive, significance test (F test), multiple linear regression, determination coefficient. Testing the classic assumption have 4 stages, that is autocorrelation test, multicollinearity test, normality test, and heteroscedasticity test. The results showed that: (1) There are significant influence between Institutional Ownership and Firm Size to Income Smoothing. (2) No significant effect between Firm Age to Income Smoothing. (3) Simultaneously a significant between Institutional Ownership, Firm Size and Firm Age on Income Smoothing.